Teacher Exemplarity and Strategies for Students' Moral Development in Islamic Diaspora Education - Farhan Afif Al Kindi; Sandi Pratama; Hendra Nelva Saputra (Jurnal Kajian Islam Interdisipliner, 2026)
This study aims to examine the relationship between teacher role modeling and students’ moral development strategies at SB Muhammadiyah Kepong Malaysia, an Islamic diaspora educational institution facing the challenge of character formation within a multicultural environment. The research employed a quantitative correlational design involving all teachers as respondents through a total sampling technique. Data were collected using Likert-scale questionnaires measuring teacher role modeling and students’ moral development strategies and were analyzed using descriptive statistics and Pearson Product-Moment correlation. The findings reveal that teacher role modeling was rated at a very high level (M = 4.64), as were the strategies for students’ moral development (M = 4.74). The Pearson correlation test yielded a coefficient of r = 0.834, indicating a very strong positive relationship between the two variables. These results suggest that the better the teacher’s role modeling, the more effective the implementation of students’ moral development strategies. The most influential dimensions of role modeling include honesty, discipline, exemplary worship practices, patience, and consistency between words and actions. This study highlights teacher role modeling as a key determinant of successful moral development in the context of Islamic diaspora education. Therefore, strengthening the school’s religious culture, promoting habitual worship practices, monitoring student behavior, and fostering sustainable collaboration between schools and parents are essential for consistently instilling moral values in students’ daily lives.